Chemotherapy‐induced hepatitis B reactivation in lymphoma patients with resolved HBV infection: A prospective study. Issue 6 (14th April 2014) - Hsu, Chiun; Tsou, Hsiao‐Hui; Lin, Shyh‐Jer; Wang, Ming‐Chung; Yao, Ming; Hwang, Wen‐Li; Kao, Woei‐Yau; Chiu, Chang‐Fang; Lin, Sheng‐Fung; Lin, Johnson; Chang, Cheng‐Shyong; Tien, Hwei‐Fang; et al.
<x xml:space="preserve">Abstract</x> Fatal hepatitis B virus (HBV) reactivation in lymphoma patients with "resolved" HBV infection (hepatitis B surface antigen [HBsAg] negative and hepatitis B core antibody [anti‐HBc] positive) can occur, but the true incidence and severity remain unclear. From June 2009 to December 2011, 150 newly diagnosed lymphoma patients with resolved HBV infection who were to receive rituximab‐CHOP (cyclophosphamide, doxorubicin, vincristine, prednisolone)‐based chemotherapy were prospectively followed. HBV DNA was checked at baseline, at the start of each cycle of chemotherapy, and every 4 weeks for 1 year after completion of rituximab‐CHOP chemotherapy. Patients with documented HBV reactivation were treated with entecavir at a dosage of 0.5 mg/day for 48 weeks. HBV reactivation was defined as a greater than 10‐fold increase in HBV DNA, compared with previous nadir levels, and hepatitis flare was defined as a greater than 3‐fold increase in alanine aminotransferase (ALT) that exceeded 100 IU/L. Incidence of HBV reactivation and HBV‐related hepatitis flares was 10.4 and 6.4 per 100 person‐year, respectively. Severe HBV‐related hepatitis (ALT >10‐fold of upper limit of normal) occurred in 4 patients, despite entecavir treatment. Patients with hepatitis flare exhibited significantly higher incidence of reappearance of HBsAg after HBV reactivation (100% vs. 28.5%; P = 0.003). Conclusion: In lymphoma patients with resolved HBV infections, chemotherapy‐induced HBV reactivation is not uncommon, but can be managed with regular monitoring of HBV DNA and prompt antiviral therapy. Serological breakthrough (i.e., reappearance of HBsAg) is the most important predictor of HBV‐related hepatitis flare. (Hepatology 2014;59:2092–2100)